The economic impact of productivity maintenance research: breeding for leaf rust resistance in modern wheat - Marasas, Carissa N.; Smale, Melinda; Singh, R. P. (Wiley, 2003)
This paper reports the results of a study undertaken to estimate the economic impact in developing countries of efforts by the International Maize and Wheat Improvement Center (CIMMYT) to breed leaf rust resistant spring bread wheat varieties since 1973. The challenge in estimating these benefits lies in the pathogen's ability to mutate to new races, which may infect previously resistant varieties. Genetic resistance, rather than fungicide application, is the principal means of controlling leaf rust in developing countries. Whereas productivity enhancement is often estimated in terms of yield gains and increased supply, productivity maintenance is measured in terms of the yield losses avoided by the research investment. The internal rate of return on CIMMYT's research investment was estimated at 41%. When discounted by 5%, the net present value was US$ 5.36 billion in 1990 dollars, and the benefit‐cost ratio was 27:l. These findings emphasise the economic importance of maintenance research in crop breeding programs.